Inflammation versus regulation: how interferon-gamma contributes to type 1 diabetes pathogenesis - De George, David J.; Ge, Tingting; Krishnamurthy, Balasubramaniam; Kay, Thomas W. H.; Thomas, Helen E. (Frontiers in Cell and Developmental Biology, 2023)
Type 1 diabetes is an autoimmune disease with onset from early childhood. The insulin-producing pancreatic beta cells are destroyed by CD8+ cytotoxic T cells. The disease is challenging to study mechanistically in humans because it is not possible to biopsy the pancreatic islets and the disease is most active prior to the time of clinical diagnosis. The NOD mouse model, with many similarities to, but also some significant differences from human diabetes, provides an opportunity, in a single in-bred genotype, to explore pathogenic mechanisms in molecular detail. The pleiotropic cytokine IFN-gamma is believed to contribute to pathogenesis of type 1 diabetes. Evidence of IFN-gamma signaling in the islets, including activation of the JAK-STAT pathway and upregulation of MHC class I, are hallmarks of the disease. IFN-gamma has a proinflammatory role that is important for homing of autoreactive T cells into islets and direct recognition of beta cells by CD8+ T cells. We recently showed that IFN-gamma also controls proliferation of autoreactive T cells. Therefore, inhibition of IFN-gamma does not prevent type 1 diabetes and is unlikely to be a good therapeutic target. In this manuscript we review the contrasting roles of IFN-gamma in driving inflammation and regulating the number of antigen specific CD8+ T cells in type 1 diabetes. We also discuss the potential to use JAK inhibitors as therapy for type 1 diabetes, to inhibit both cytokine-mediated inflammation and proliferation of T cells.